The Role of Special Guidance Institutions for Children in Achieving the Rehabilitation Objectives for Juveniles in Conflict with the Law in Pangkalpinang, Bangka Belitung Province. - Alkok Marya; Junaidi Abdillah (Dinasti Research, 2025)
The treatment of children in conflict with the law is a critical component of efforts to achieve restorative justice, as mandated by Law No. 11 of 2012 on the Juvenile Criminal Justice System (SPPA). The Special Child Development Institution (Lembaga Pembinaan Khusus Anak, LPKA) Class II Pangkalpinang holds a strategic role in carrying out rehabilitation programs aimed at protecting children’s rights and preparing them for reintegration into society. This study employs an empirical juridical method with a qualitative approach, incorporating document analysis, interviews, and direct observation of the rehabilitation programs implemented at LPKA Class II Pangkalpinang. The findings reveal that although rehabilitation programs, such as formal education, skills training, and personality development, are conducted in line with the principles of restorative justice, their effectiveness is hindered by limitations in human resources and supporting facilities. These constraints significantly affect the psychosocial development of the juvenile inmates. This study concludes that the rehabilitation programs at LPKA Class II Pangkalpinang have made positive contributions to fulfilling the rights of children in conflict with the law. However, achieving optimal outcomes necessitates improving staff competencies, providing adequate facilities, and strengthening cross-sectoral cooperation to fully realize the goals of the rehabilitation programs. The findings contribute to the existing body of knowledge on juvenile justice systems by offering an in-depth analysis of the practical challenges faced in implementing restorative justice principles within institutional settings. Additionally, this study provides actionable insights for policymakers and practitioners to enhance the effectiveness of rehabilitation programs, emphasizing the need for systemic and multi-sectoral collaboration to support the reintegration process.